Integrasi Jaringan Jalan dan Drainase di Perumahan Bumi Aroepala, Kabupaten Gowa - Iffahni Iffahni; Wiwik Wahidah Osman; Mimi Arifin (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
Housing and settlements developed very strong in suburban. Suburban developments also occured along Tun Abdul Razak street, currently there were 8 housing clusters built along Tun Abdul Razak street, one of them was Bumi Aroepala Housing. When rain falls, there were inundations at several points in this housing. This study aims to identified the development process of Bumi Aeropala Housing from 2008 to 2018, identified conditions of road and drainage networks integration in Bumi Aroepala Housing, and formulated direction for road and drainage network integration in Bumi Aroepala Housing. Spatial analysis wasused to determined the development of housing, quantitative qualitative analysis was used to identified the quantity and quality of road and drainage network integration in Bumi Aroepala Housing, and comparative analysis was used to compared the problems and directives that should be done. The results showed that the development of Bumi Aroepala Housing land area from 2008-2018 increased 91% or 95,256 m², while the number of buildings increased 98% or 527 units. In this housing there were no pedestrian way on the main residential road. There were several damaged roads and there were 3 roads that should be connected. Besides that there were no drainage network at 3 points in this housing and there were some drainage that not in the good conditions. Directions for this study were road repairs and the making of pedestrian way on the main residential roads, adding drainage networks at the location points that didin’tt have drainage and implemented the concept of sustainable drainage. There were 3 sustainable drainage concepts that can be implemented in this housing, they were rain garden, infiltration strip, and permeable surface.